Localités : localisation des écrits et production locale d’actions - Introduction - Mathilde Bombart; Alain Cantillon (Les Dossiers du GRIHL)
The issue of « local » is here considered in relation to the collective works of the Grihl. It invites to question the way how writing works (“literary” works but not only) can be related to places, spaces, loci – as a result of specific localization processes. It also carries out an inquiry into the scale(s) of analysis put in place to study texts and books, and the appropriate contexts that have to be built to bring into light their actions and meanings.